Fractures of the humerus during arm wrestling - Bumbaširević, Marko Ž.; Lešić, Aleksandar R.; Andjelković, Sladjana Z.; Palibrk, Tomislav D.; Milutinović, Suzana M. (Vojnosanitetski pregled, 2014)
Background/Aim. Humeral shaft fractures may occur as a result of arm wrestling. The aim of this study was to present our treatment of humerus fracture sustained during arm wrestling. Methods. A total of six patients, aged 22 to 48, were treated at our department form January 2008 to January 2010 with open reduction and internal fixation and with hanging arm casts. A review of all the relevant literature on the subject was also presented. Results. In all the cases, the fractures healed and function returned to normal. No patient had any neural or vascular compromise. Conclusion. Closed and operative treatments were equally successful in all reported cases.